Implementasi Safety Management System ( SMS ) Pada Jasa Layanan Lalu Lintas Udara - Peniarsih, Peniarsih (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2015)
A plane crash can occur due to many factors, including the aircraft itself a factor, the factor of human error, weather factors, or even ketida¬kberfungsian of airport facilities. Factors ¬faktor basically it is the responsibility of each relevant parties such as the airport as an institution pen¬gelola provider of air traffic services (air traffic service provider), airlines, and the Department of Transportation as the regulator. Weather factors, which may actually be diantisi¬pasi, often the scapegoat cause of the accident. Meanwhile several accidents, involving airline would indicate that it is not serious enforcement of safety standards and procedures of government. This prompted the company as a business cost, especially providers of air traffic services or kebandaraan made various efforts to reform the management system mau¬pun service to consumers. Management of service quality teaching that any form and regardless of the situation as a service provider, there is no reason for not trying to satisfy the public. In this case, the implementation of a Safety Management System, hereinafter referred to as the Safety Management System (SMS) became the standard size is calculated in the management of airport services management. PT (Persero) Angkasa Pura II has approximately five thousand personnel who move in 12 airports, running hundreds of standards, rules and producer, applying thousands of manuals, and local regulations as well as